Interfacial Dynamic Velocity for Solar Cell Characterization - J. Farah; B. Azar; A. Khoury; P. Mialhe (Active and Passive Electronic Components)
A new parameter for solar cell characterization has been introduced. The n–P junction has been considered as an active interface and an interfacial dynamic velocity is defined at the base boundary of the space charge region. We show that this interracial dynamic velocity depends on the base width, base doping profile, and the recombination velocity at the device back surface. Additionally, it is shown to be a function of the operating conditions such as the applied potential and the illumination level.